Brassica Oilseeds Breeding and Management - Kumar Arvind; Banga SS; Meena PD; Kumar PR; Vinod Kumar (Journal of Oilseed Brassica, 2026)
The book “Brassica Oilseeds Breeding and Management” presents an unprecedentedlythorough collection of information on the basic and strategic research of breeding andmanagement of Brassica oilseeds crops. This book is a result of an imperative need anddemand from the researchers, teachers, students, and interest by the publishers (CABI) tobring out the comprehensive information on Brassica oilseeds crops. It covers and integratesworldwide literature in the field of oilseed Brassica research upto 2015, setting it apart fromother books that are only of regional importance. By compiling information of decades fromformerly scattered research into a single globally-minded volume, Brassica Oilseeds Breedingand management provides these deeply desired updates and improvements.It is inspirational that Prof. Arvind Kumar, Vice Chancellor, Rani Lakshmi Bai Central AgriculturalUniversity, Jhansi, India, Prof. Surinder S. Banga, ICAR-National Professor, Punjab AgriculturalUniversity, Ludhiana, India, Dr. Prabhu Dayal Meena, Principal Scientist, ICAR-Directorateof Rapeseed-Mustard Research, Bharatpur, India and Dr. Priya Ranjan Kumar, Founder Director, National ResearchCentre on Rapeseed-Mustard, Bharatpur, India has bring out this useful book Brassica Oilseeds Breeding and Management.The book, foreword written by Prof. Ting-Dong Fu, Huazhong Agricultural University, Institute of Crop Genetics &Breeding, Wuhan, China. The book is published by internationally repute publisher CABI and priced at $144, could beconsidered and recommended for the institutes/ university libraries, personal collection for teaching and researchoilseeds Brassica.